Boundary Layer Flow over a Vertical Plate - Mohd Johari, Desy Farisa; Md Shab, Noorzehan Fazahiyah (Enhanced Knowledge in Sciences and Technology, 2022)
The focus of this research is to study the nonlinear boundary layer problem by considering the natural convection of heat transfer about a vertical plate. The nonlinear coupled partial differential equations of momentum and energy equation are transformed into nonlinear ordinary differential equation by using similarity transformation. This study highlights a comparison between two different numerical methods in solving two-point boundary layer problem to analyze the reliability and efficiency of each method. The method used in this research is bvp4c method which is one of the built-in programs in MATLAB for solving boundary layer problem and the comparison are made with shooting method from the previous research. The velocity distributions and temperature distributions are illustrated. The result obtained shows a good agreement between two methods in solving the boundary layer problem.